DEVELOPING SCIENCE PROCESS SKILLS (SPS) INSTRUMENTS FOR VOCATIONAL SCHOOL STUDENTS USING CBT - Widodo Widodo; Abdurrahman Abdurrahman; Undang Rosyidin; Agus Suyatna (Science Education, Institut Agama Islam Negeri Ponorogo, 2020)
This study aimed to develop a Science Process Skills (SPS) instrument using CBT on heat matter. The method implemented was Borg & Gall Research and Development model. The preliminary stage data proved that instruments to measure SPS using CBT were required. In design & product development stage, instruments were validated by experts. Validation score of media was 84.5%, while matter score was 80%, and language score was 84%. The product testing stage was conducted at a vocational school in Lampung Province. The SPS instruments tested using CBT was done in 4 stages, i.e. the expert, the small group, the field and the instrument test stages. The results of the expert analysis test showed a percentage score of 85.25% or very eligible. The results of limited and field trials showed results of 86.5% and 81.5% or very interesting. The results of small group trials through students’ responses were 86.5% while field trials were 81.5% or very interesting. The instruments test resulted 15 valid instruments of 20 prepared questions, the reliability (r11) was 0.97 or very reliable. The discrimination power of 15 questions was categorized as good. The difficulty level showed that 7 questions were easy while 8 others were sufficient category